Language effects on semantic fluency test performance among South African adults - Kwinana, Anathi (Department of Psychology, 2021)
Issues around the cultural fairness of cognitive tests and their administration are becoming increasingly important as the global spread of neuropsychological practice quickens. Most of these tests are developed and standardized in high-income countries of the global north, and so when used in low- and middle-income countries (LAMICs) of the global south they are susceptible to influence by non-organic factors. Of relevance for this thesis is that these factors include language of test administration (e.g., whether the test is administered in the participant's home language or language of education) and the language profile of the test-taker (e.g., whether the person is multilingual). Semantic fluency tests are a standard component of many neuropsychological test batteries (e.g., those used to detect various forms of dementia), and are commonly administered in LAMICs without due regard for language influences on performance. Hence, the aim of this research was to investigate the influence of language of test administration on semantic fluency test performance in a sample of multilingual students from an English-medium South African university. Participants were 75 balanced English-isiXhosa bilinguals who were administered singlelanguage and forced-switching semantic fluency tests in both languages, as well as a freeswitching semantic fluency test. Results showed that, across test conditions, participants generated more words when administered the tests in English than in isiXhosa. Analyses also showed that, during the isiXhosa but not English administration, participants performed better under free-switching than forced-switching or single-language conditions. The strongest conclusion one can draw from these observations is that test administrators must ensure that test takers are assessed in a language that allows them to demonstrate their optimal cognitive capacity, and that therefore a determination of language proficiency in each of the test-taker's languages is a necessary prerequisite for assessment. This step is especially important in countries, like South Africa, that are home to many multilingual individuals.